Atherosclerotic Cardiovascular Disease (ASCVD) risk assesment among healthy Indonesian Navy Personnel in East Java, Indonesia - Sinurat Josua Maruli; Nugraha Krishna Ari; Budiharto Tanto (ARKA INSTITUTE, 2023)
Indonesia, as the largest archipelagic country, has a military population of its own. Atherosclerotic Cardiovascular Disease (ASCVD) are common in in Indonesian Navy personnel populations, and recent studies reported an increasing ofits prevalence.However, the data on specific navy military populations are still limited. This study aims to assess ASCVD risk on Indonesian navy personnel. This study use yearly medical check-up data of the Indonesian navy with high rank (fleet commander) aged 25-60 years old in period of January-August 2023. Those who already diagnosed with coronary artery disease were excluded. We use Framingham risk score and EUROS II Score to assess the ASCVD risk among samples. A total of 503 samples were recruited, 474 were male. Mean of age was 45 y.o, predominantly they were active smoker (64,8%) and overweight (44,5%). Among men’s population, the Framingham risk score shows almost half of the samples are at medium risk of ASCVD (40,16%), while a small percentage (17,3%) are at high risk as well as EuroSCORE II show remarkbly 62,21% of high ASCVD risk. The medium to high ASCVD risk among Indonesian Navy personnel need further attention and evaluation. A failure to give a decent preventive intervention may increase the burden of ASCVD in the future.